The Sources of Taxation in Bologna in the 14th Century - Clément Carnielli (Journal of Open Humanities Data)
Many studies have established the creation of new forms of taxation in Medieval Bologna, the increase of tax revenue between the 13th and 14th centuries, and the contemporary aggravation of economic inequalities. Based on doctoral research on the relations between fiscal policies and political inequalities at the end of the 14th century, this research paper describes the building of a database of all known contributions in Bologna in the 14th century and highlights what such a tool can offer. The first objective of the database is to present the pace and social distribution of taxation in the Bolognese Trecento. Another main interest is to gather all the pertinent documentation on taxation, which is still scattered in several series. These registers are not always linked, and some simply bear and indirect traces of the subject of our interest, but they are an initial approach to the documentary links around which taxation was organized, to the various practices of the officers, and the several functions of public taxation, beyond the basically fiscal aspect.